2017
DOI: 10.1186/s13024-017-0194-8
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 channels promote astrocytic Ca2+ hyperactivity and synaptic dysfunction mediated by oligomeric forms of amyloid-β peptide

Abstract: BackgroundExcessive synaptic loss is thought to be one of the earliest events in Alzheimer’s disease (AD). However, the key mechanisms that maintain plasticity of synapses during adulthood or initiate synapse dysfunction in AD remain unknown. Recent studies suggest that astrocytes contribute to functional changes observed during synaptic plasticity and play a major role in synaptic dysfunction but astrocytes behavior and involvement in early phases of AD remained largely undefined.MethodsWe measure astrocytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 51 publications
3
73
1
Order By: Relevance
“…Other components include menthofuran, 1,8-cineol, terpenoids, and flavonoids such as eriocitrin, hesperidin, and kaempferol 7-O-rutinoside [35]. The main cellular receptor for peppermint odor is transient receptor potential cation channel subfamily A member 1, which is associated with AD [36,37]. Peppermint (Mentha piperita) essential oil, which has high levels of menthol/menthone and characteristic in vitro cholinergic inhibitory, calcium regulatory, and GABAA/nicotinic receptor-binding properties, beneficially modulated performance on demanding cognitive tasks and attenuated the increase in mental fatigue associated with extended cognitive task performance in healthy adults [38].…”
Section: Discussionmentioning
confidence: 99%
“…Other components include menthofuran, 1,8-cineol, terpenoids, and flavonoids such as eriocitrin, hesperidin, and kaempferol 7-O-rutinoside [35]. The main cellular receptor for peppermint odor is transient receptor potential cation channel subfamily A member 1, which is associated with AD [36,37]. Peppermint (Mentha piperita) essential oil, which has high levels of menthol/menthone and characteristic in vitro cholinergic inhibitory, calcium regulatory, and GABAA/nicotinic receptor-binding properties, beneficially modulated performance on demanding cognitive tasks and attenuated the increase in mental fatigue associated with extended cognitive task performance in healthy adults [38].…”
Section: Discussionmentioning
confidence: 99%
“…Since TRPA1 can be triggered by several noxious stimuli, including inflammation, tissue damage or oxidative stress on one hand, and astrocytes influence the extent of this toxin-induced demyelination on the other [29], we assumed that this receptor might modulate the demyelination process. Numerous earlier studies have provided substantial morphological and functional evidence that astrocytes express the TRPA1 receptor, functioning as a regulator of resting Ca 2+ levels [8,9,24,30,31]. In a very recent study, Oh et al, using the cell-type-specific gene-silencing and ultrasensitive sniffer-patch techniques, identified astrocytes as the cellular target and TRPA1 as the molecular sensor for the low intensity, low frequency ultrasound (LILFU).…”
Section: Discussionmentioning
confidence: 99%
“…TRPA1 was first identified in mouse hippocampal astrocytes and associated with Aβ-mediated Ca 2+ signaling (Figure 2F; Lee et al, 2016). The cause of Aβ oligomer-mediated fast Ca 2+ signaling appears to be the hyperactivation of TRPA1 (Bosson et al, 2017). TRPA1induced Ca 2+ signaling initiates the release of inflammatory factors such as PP2B, NF-κB, and NFAT (Figure 2F).…”
Section: Trpa1mentioning
confidence: 99%
“…Until now, the role of TRPA1 in neurons has only been reported on with respect to pain and inflammation, although recent studies have revealed a potential involvement in AD pathogenesis. Deposition of Aβ is an important factor in the exacerbation of AD, and soluble Aβ oligomers mediate fast and widespread Ca 2+ influx in astrocytes (Bosson et al, 2017). TRPA1 was first identified in mouse hippocampal astrocytes and associated with Aβ-mediated Ca 2+ signaling (Figure 2F; Lee et al, 2016).…”
Section: Trpa1mentioning
confidence: 99%